Self-assembled hydrogel fiber bundles from oppositely charged polyelectrolytes mimic micro-/nanoscale hierarchy of collagen - Sant, Shilpa (2017)
Fiber bundles are present in many tissues throughout the body. In most cases, collagen subunits spontaneously self-assemble into a fibrilar structure that provides ductility to bone and constitutes the basis of muscle contraction. Translating these natural architectural features into a biomimetic scaffold still remains a great challenge. Here, a simple strategy is proposed to engineer biomimetic fiber bundles that replicate the self-assembly and hierarchy of natural collagen fibers. The electrostatic interaction of methacrylated gellan gum with a countercharged chitosan polymer leads to the complexation of the polyelectrolytes. When directed through a polydimethylsiloxane channel, the polyelectrolytes form a hierarchical fibrous hydrogel demonstrating nanoscale periodic light/dark bands similar to D-periodic bands in native collagen and align parallel fibrils at microscale. Importantly, collagen-mimicking hydrogel fibers exhibit robust mechanical properties (MPa scale) at a single fiber bundle level and enable encapsulation of cells inside the fibers under cell-friendly mild conditions. Presence of carboxyl- (in gellan gum) or amino- (in chitosan) functionalities further enables controlled peptide functionalization such as Arginylglycylaspartic acid (RGD) for biochemical mimicry (cell adhesion sites) of native collagen. This biomimetic-aligned fibrous hydrogel system can potentially be used as a scaffold for tissue engineering as well as a drug/gene delivery vehicle.